WRITTEN CORRECTIVE FEEDBACK ON THE PROCESS OF STUDENTS’ RESEARCH PROPOSAL WRITING - Satriani, Estika; Yulianto (International Journal of Psychosocial Rehabilitation, 2020)
One of the activities that students’ writing skills need to be corrected is error in writing process. Written Corrective Feedback can be effective technique in improving students’ writing. This research aimed to describe the types of correction feedback given by the lecturer, students’ responds and students’ perceptions in utilizing WCF to correct their research proposal writing. Participant selected 10 students of 2017 academic year who propose the research proposal as the final projects. This study applied a descriptive qualitative method. The researcher analysed 10 students’ research proposals to know the types of WCF in correcting research proposal writing. Interview used to know students’ respond and perception toward using WCF. Research findings identified four forms of written corrective feedback that the lecturer used to provide guidance. 52% written correction feedback was classified as direct corrective feedback, 6% feedback was classified as indirect corrective feedback, 26% feedback was classified as focused feedback, and 16% feedback was classified as unfocused corrective feedback. These finding also supported by the result of interview which were 6 of 10 students preferred direct written corrective feedback.Students said that clear correction feedback provides specific instructions to students on how to correct their errors.